Get clear, concise, and accurate answers to your questions on IDNLearn.com. Find accurate and detailed answers to your questions from our experienced and dedicated community members.
Answer:
[tex]2-\sqrt{3}[/tex]
Step-by-step explanation:
[tex]\begin{aligned}\dfrac{\sqrt{3}-1}{\sqrt{3}+1}\times \dfrac{\sqrt{3}-1}{\sqrt{3}-1} &=\dfrac{(\sqrt{3}-1)(\sqrt{3}-1)}{(\sqrt{3}+1)(\sqrt{3}-1)}\\\\ & =\dfrac{\sqrt{3}\sqrt{3}-\sqrt{3}-\sqrt{3}+1}{\sqrt{3}\sqrt{3}-\sqrt{3}+\sqrt{3}-1}\\\\ & =\dfrac{4-2\sqrt{3}}{2}\\\\ & = 2-\sqrt{3}\end{aligned}[/tex]